Les terres agricoles face à l'urbanisation - Plant, Roel; Maurel, Pierre; Barbe, Éric; Brennan, Jane (éditions Quae, 2018)
This work addresses the key points of the problem of land consumption by focusing on farmland in France and Australia. It suggests exploring territorial engineering â€œtoolboxesâ€ developed and used to face up to the challenge of losing farmland to urbanisation.